Experimental Measurement and Multiphysics Simulation of Tritium Transport in Neutron-Irradiated Flibe Salt. (3rd April 2023) - Dolan, Kieran; Su, Guanyu; Zheng, Guiqiu; Ames, Michael; Carpenter, David; Hu, Lin-Wen
Abstract: Predicting the distribution and release of tritium remains a technical challenge for advanced nuclear reactors with molten Flibe (2LiF-BeF2 ) salt coolants. Tritium transport models, which are currently used to forecast release behavior, are limited by uncertainty in Flibe-related tritium transport properties and by a lack of relevant benchmark experiments to test input parameters and solution methods. A new test facility has been developed at the Massachusetts Institute of Technology Research Reactor (MITR) to irradiate a molten Flibe target in an ex-core neutron beam port to further investigate tritium transport mechanisms at prototypical reactor conditions. The experiment monitored the time-dependent release of tritium from the salt-free surface and the permeation rate of tritium through the stainless steel Flibe-containing test stand. Measured results were benchmarked with a multiphysics tritium transport simulation to resolve complex effects in the test. Trends in tritium release rates from the irradiation were in agreement with the multiphysics simulation of the test, which combined computational fluid dynamics, radiative heat transfer in participating media, and tritium transport in STAR-CCM+.